Sexual orientation differences in teen pregnancy and hormonal contraceptive use: An examination across two generations - Charlton, Brittany M. (2013)
OBJECTIVES: To examine whether sexual orientation is associated with disparities in teen pregnancy and hormonal contraception use among adolescent females in two intergenerational cohorts. STUDY DESIGN: Data were collected from 91,003 women in the Nurses’ Health Study II (NHSII),born between 1947–1964, and 6,463 of their children, born between 1982–1987, enrolled in the Growing Up Today Study (GUTS). Log-binomial models were used to estimate risk ratios (RR) for teen pregnancy and hormonal contraception use in sexual minorities compared to heterosexuals and meta-analysis techniques were used to compare the two cohorts. RESULTS: Overall, teen hormonal contraception use was lower and teen pregnancy was higher in NHSII than GUTS. In both cohorts, lesbians were less likely, whereas the other sexual minorities were more likely, to use hormonal contraception as teenagers compared to their heterosexual peers. All sexual minority groups in both cohorts, except NHSII lesbians, were at significantly increased risk for teen pregnancy, with RRs ranging from 1.61 (95%CI 0.40, 6.55) to 5.82 (95%CI 2.89, 11.73). Having a NHSII mother who was pregnant as a teen was not associated with teen pregnancy in GUTS participants. Finally, significant heterogeneity was found between the two cohorts. CONCLUSIONS: Adolescent sexual minorities have been, and continue to be, at increased risk for pregnancy. Public health and clinical efforts are needed to address teen pregnancy in this population.